Los hábitos de la lectura y su incidencia en el rendimiento académico en los niños y niñas del quinto, sexto y séptimo grados del nivel de educación general básica media, de la escuela fiscal mixta Lauro Damerval Ayora del barrio La Tebaida, parroquia San Sebastián, cantón Loja en la provincia de Loja, año lectivo 2012 -2013 - Torres Quezada, Ayde Ximena (2014)
This research work entitled READING HABITS AND ITS IMPACT ON THE ACADEMIC PERFORMANCE IN CHILDREN OF THE FIFTH , SIXTH AND SEVENTH GRADE LEVEL BASIC EDUCATION MEDIA GENERAL , JOINT SCHOOL OF FISCAL LAURO Damerval AYORA LA DEL BARRIO TEBAIDA , SAN SEBASTIAN PARISH , ON THE CANTON Loja Loja Province , 2012 -2013 SCHOOL YEAR .The project in which the strategies and methodological procedures used to cultivate reading habits and their impact on academic performance in children was analyzed , taking into account the overall objective primarily as determine the lack of reading habits in students , fifth sixth and seventh grades average level Basic General Education Fiscal Primary School " Lauro Damerval Ayora, the Theban district , county and province of Loja Loja , school year 2012 - 2013 , the methods that were used to carry investigative work are scientific , deductive , analytical and statistical method. Subsequently the different techniques are applied as is applied observation guide and students of the institution , interviews applied to teachers which served mainly to tabular and get the results based on the silver test hypotheses in the research project and to obtain significant results demonstrating that teachers do not apply technical and methodological procedures that allow students to create reading habits , as well as lack of motivation is an important factor in predisposing to learning to read and especially allows they can practice daily reading, as well as achieve cultivate reading habits and especially help him to improve reading comprehension and academic performance . It is recommended that students achieve significantly improve reading teachers must insert into the classroom recreational books according to interest the practice of reading , especially applied methodological strategies and procedures for teaching effectively coadyuden correct reading in the teaching - learning in education